Legal aspects of providing social welfare during a state of natural disaster caused by flooding - Cendrowicz, Dominika (Studia Iuridica Toruniensia, 2025)
In September 2024, parts of Poland were hit by a tragic flood. To deal with its effects, a state of natural disaster was declared in parts of the country. Floods have previously occurred in the country, consistently exerting significant adverse effects on the affected populations. Phenomena such as flooding also pose numerous challenges for social welfare institutions. The publication aims to analyze the prerequisites for obtaining social welfare by flood victims, as well as to characterize the most important forms of social welfare that the legislature regulates in a crisis situation or state of disaster caused by flooding. The aim of the publication is also to answer whether the legal regulation of the Act of March 12, 2004 on social welfare answers the challenges posed by the occurrence of events such as flooding, and if so, whether the forms of aid specified therein can be considered adequate to the reasons justifying their provision.